Cyber‑Physical Systems Approach to Risk Mitigation in Multivendor Subsea Control Architecture Integration and Operational Reliability - Malvern Iheanyichukwu Odum,; Iduate Digitemie Jason,; Dazok Donald Jambol, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of multivendor subsea control architectures presents significant challenges to operational reliability due to heterogeneous hardware, diverse communication protocols, and increased cybersecurity risks. This paper proposes a cyber-physical systems approach to risk mitigation that models the complex interactions between physical subsea components and their digital control environments. The framework enables real-time monitoring, adaptive fault detection, and dynamic fault tolerance, addressing critical vulnerabilities such as interface mismatches, protocol incompatibilities, and cyber threats. By systematically identifying and prioritizing risks within the integrated architecture, the approach guides targeted mitigation strategies, improving system resilience and reducing downtime. The research further explores how cyber-physical principles can be embedded in subsea control design to enhance interoperability, modularity, and vendor collaboration. The proposed methodology offers a comprehensive pathway for operators to manage integration complexities, ensure safer offshore operations, and support future advances in autonomous control. Future directions include real-time CPS monitoring, adaptive control systems, and cross-domain risk frameworks that extend beyond subsea environments. This work contributes both theoretically and practically to the evolution of reliable, integrated subsea control systems in increasingly complex offshore infrastructures.
Keywords: Cyber-Physical Systems; Subsea Control Architecture; Multivendor Integration; Risk Mitigation; Operational Reliability; Offshore Systems